A field guide to the wildlife of South Georgia - Burton, Robert, 1941-; Croxall, J. P. (WildGuides., 2012)
South Georgia is rich in wildlife and spectacular scenery, and it is a prime destination spot on most Antarctic tours. This beautifully illustrated field guide depicts the birds, mammals, insects, flowering plants, and other vegetation found in this unique part of the world. It features 368 full-color photographs of more than 180 species, including 65 species of birds, 20 species of sea mammals, nearly 60 species of insects, and more than 40 species of flowering and nonflowering plants. Detailed species accounts describe key identification features, with information on status, behavior, threats, and distribution. This one-of-a-kind photographic guide also includes introductory chapters on South Georgia's geography, climate, ecology, and conservation.Features 368 photos of more than 180 species Covers birds, sea mammals, insects, and plants Provides detailed species accounts Includes chapters on geography, climate, ecology, and conservation The only photographic field guide to focus specifically on South Georgia.